The Effectiveness of Group Intervention on Enhancing Cognitive Emotion Regulation Strategies in Breast Cancer Patients: A 2-Year Follow-up. (June 2016) - Hamama-Raz, Yaira; Pat-Horenczyk, Ruth; Perry, Shlomit; Ziv, Yuval; Bar-Levav, Ruth; Stemmer, Salomon M.
Purpose . To evaluate the long-term effect of group intervention on enhancing cognitive emotion regulation (CER) strategies in female patients with early-stage breast cancer. Methods . The sample included 174 patients who were diagnosed with early-to-mid stage breast cancer, completed adjuvant therapy, and agreed to fill out demographic and cognitive emotion regulation questionnaires (CERQ). About half of the patients (86, 49.4%) chose to participate in an 8-session group intervention (intervention group) while the others (88, 50.6%) did not (comparison group). The structured intervention for enhancing coping strategies with special emphasis on emotion regulation was conducted at the oncology unit at Rabin Medical Center by 2 experienced therapists. Preliminary effects on CER evaluated 6, 12, and 24 months postintervention were compared to the CER of a group of patients that opted not to participate in the group intervention. Results . In the intervention group, the long-term effect (from baseline to 24 months) was assessed using the mix models module. Significant interaction effects were found for both the Negative CER scales ( F (3, 268  , 404) = 3.66, P = .01) and for the Positive CER scales ( F (3, 271  , 660) = 5.12, P = .002). No statistically significant differences in socio-demographic characteristics and medical variables were observed between the intervention and comparison groups. Conclusion . Our findings indicate that a group intervention aimed at empowerment of coping strategies had positive long-term outcomes that reinforce adaptive coping strategies and improve less effective strategies of cognitive emotion regulation.